Los bordes de la escritura: la crónica modernista de Arturo Ambrogi - Pérez Méndez, Kevin (2017)
This article proposes an approach to a series of texts compiled in Marginales de la Vida (1963), a book published by Salvadorian writer Arturo Ambrogi in 1912, from the existing links on them between the modernist influence and the journalistic career developed by its author. The main objectives are to explore Arturo Ambrogi`s literary production through an analysis of the tensions generated when locating part of his writing in the Salvadorian, Central American and Latin American literature from the early XX century, and to postulate the possible presence of a literary hybrid that escaped from the visions followed by other contemporary writers of the region during the studied period.